The Saami Language Situation in Russia - Scheller, Elisabeth (2011)
The article gives an overview of the Saami language situation in Russia, there people use four Kola Saami languages or at least have some competence in them (Kildin Saami, Ter Saami, Skolt Saami and Akkala Saami). Since the 1990's, also North Saami has been used among Kola Saami community members. Today, all four Kola Saami languages are seriously threatened by a language shift from Saami to Russian. However, a revitalization process of Kildin Saami is going on. The article starts with a general introduction about the Saami, who are one of the indigenous people and minorities in the Russian Federation. After that, sources of data will be presented and categories of language competence as well as categories of language users, their numbers and their visibility inside and outside the language community will be discussed. Numbers of Saami language users in Russia are presented in a table. A description of the actual Saami language situation(s) in Russia describing each language variation separately follows. Finally, conclusions are drawn about the language situation with regard to the potential for a possible language revitalization, which is the main focus of the article.